Surface and interface analysis of poly-hydroxyethylmethacrylate-coated anodic aluminium oxide membranes - Ali, N.; Duan, X.; Jiang, Z.; Goh, B.; Lamb, R.; Tadich, A.; Poinern, G.; Fawcett, D.; Chapman, P.; Singh, P. (Elsevier BV North-Holland, 2014)
The surface and interface of poly (2-hydroxyethylmethacrylate) (PHEMA) and anodic aluminium oxide (AAO) membranes were comprehensively investigated using Near Edge X-ray Absorption Fine Structure (NEXAFS) spectroscopy. It was found that 1s→ π* (C O) and 1s→ σ* (C-O) transitions were dominant on the surface of both bulk PHEMA polymer and PHEMA-surface coated AAO (AAO–PHEMA) composite. Findings from NEXAFS, Fourier-Transform Infrared (FTIR) and X-ray Photoelectron Spectroscopy (XPS) analyses suggest the possibility of chemical interaction between carbon from the ester group of polymer and AAO membrane.